Investigating the predictive ability of FLI for non-alcoholic fatty liver disease involvement - Rafieian, Bahare; hatami, behzad; Abdi , Saeed (Student Research in Translational Medicine, 2022)
Background and aim: non-alcoholic fatty liver disease (NAFLD) is one of the common concerns in the world. This disease has a correlation with obesity, type 2 diabetes, metabolic syndrome, and other diseases. So, prediction and diagnosis of NAFLD is important. Fatty liver index can be used as a good method for prediction of NAFLD involvement but there are few evidences about it. The aim of this study was to investigate the prediction and diagnostic power of FLI to predict and diagnosis of NAFLD. Materials and Methods: in this diagnostic study, patients who were referred to our hospital from 2020 to 2021 were assessed. Patients with NAFLD (N=108) were compared with normal people (N=220) based on age, sex, anthropometric parameters, laboratory data, and FLI. Result: the mean age among all participants was 45.62 ± 10.93 years. There were significant differences between NAFLD group and normal group about age, sex, height, weight, BMI, waist circumference, diabetes and hypertension history, TG, LDL, AST, ALT, ALK,GGT. The sensitivity, specificity, and accuracy of FLI in diagnosis of NAFLD were 73.15%, 81.36%, and 78.66%, respectively. The best cut-off point based on ROC analysis and Youden index for differentiation of grade 1 from grade 2 was 69.5 and the best cut-off point for differentiation of grade 2 from grade 3 was 72.5 when the high FLI level considered as 60. Conclusion: FLI is good method for prediction and diagnosis of NAFLD.